Operational Feasibility Assessment of Geothermal Heat Harnessing Systems - Ferenc, Ferenc; Fórián, Zsolt Lajos (International Journal of Engineering and Management Sciences, 2021)
Renewable energy sources are now essential to establish sustainable development. This paper examines one kind of source the geothermal energy. For geothermal energy when combined with a heat pump COP can be used for evaluation. For solely geothermal sources different approach is needed thus in the paper, a new geothermal heat production coefficient is used to examine the operational feasibility. For the assessment, many hypothetical buildings were created to model their heat demands. Two types of calculation methods are used for heat demand calculation. Based on the results, the maximum depth of a geothermal borehole and economically critical qualitative coefficient was concluded.